Unravelling Accident Patterns, Causes, and Solutions for Foreign Workers in Construction Industry: A Case Study in Sarawak, Malaysia - Ismani, Nur’ Isma; Jabar, Izatul laili (Research in Management of Technology and Business, 2024)
The construction sector in Sarawak, Malaysia heavily relies on foreign labor for its labor-intensive projects, which significantly contributes to the region's economic advancement. However, the safety and welfare of these workers are frequently compromised due to substandard working conditions, inadequate safety measures, and lack of enforcement on occupational safety and health (OSH) regulations. This study aims to propose an effective strategy to improve the safety of foreign workers in Sarawak's construction industry by examining common accidents, identifying root causes, and recommending safety enhancement approaches through quantitative methodologies, primarily employing questionnaires distributed to construction industry stakeholders in Sarawak. The findings highlighted that scaffolding collapse as the prevalent accident due to inadequate safety training. Recommendations for rigorous enforcement of OSH regulations, increased availability of safety training, and enhanced employer accountability are emphasized. Ultimately, the study highlighted the importance of comprehensive safety measures in the construction industry to ensure the well-being of all stakeholders specifically the foreign workers and at the same time ensuring the project success.